Global responses to chronic diseases: What lessons can political science offer? - Chantal Blouin (Administrative Sciences, 2012)
Designing and adopting a global response to address the rise of chronic diseases in both the industrial and developing world requires policymakers to engage in global health diplomacy. In the context of the recent United Nations' High-Level Summit on Non-Communicable Diseases, the paper first reviews the rationale for collective action at the global level to address the rise of non-communicable diseases (NCDs), given the perceived limited cross-border dimensions of NCDs. Secondly, based on the social sciences literature studying policymaking at the domestic and international level, this article highlights recommendations on how to engage during the main phases of the policy process: agenda-setting, policy development and adoption.
Keywords: 350; global health; diplomacy; non-communicable diseases; chronic diseases; policy; global collection action